ANALYSIS OF FACTORS AFFECTING CUSTOMER SATISFACTION TO GET CUSTOMER LOYALTY - Hudaya, Agung; Djumarno, Djumarno; Djubaedah, Siti (Dinasti International Journal of Digital Business Management, 2021)
The digital era brings humanity into life easier, even in ordering food or drinks in the modern era is very easy. Because it is supported by sophisticated technology, it will support a more aggressive economy. However, this is an aspect that is considered by researchers, with an economy supported by sophisticated technology, there will be quite tight competition, many MSME companies feel helped but many small companies are threatened due to lack of knowledge about strategies for customer satisfaction related to product quality and price perception. The variable behind customer satisfaction is expected to bring customers into loyal customers. This study required 130 customers as respondents in the study who would be randomly selected to answer the research questionnaire